LINEAR INTERPOLATION AS A BASELINE TOOL FOR ONLINE RIDE-HAILING FARE ESTIMATION DURING PEAK HOURS - Prima Yalesta Sarumaha; Mutaqin Akbar (Bulletin of Network Engineer and Informatics, 2026)
The dynamic pricing system on Grab causes frequent fare fluctuations, complicating travel budget planning. This study analyzes GrabBike Reguler fare patterns from Campus 3 of Universitas Mercu Buana Yogyakarta (UMBY) to Mirota Kampus Babarsari. It implements linear interpolation as a lightweight numerical baseline for rough estimation, rather than a robust predictive model. Primary data were collected through direct observation over seven days at 15-minute intervals during morning (07:00–09:00 WIB), noon (12:00–13:00 WIB), and evening (16:00–19:00 WIB) peak periods, noting rainy and non-rainy conditions. This method was deployed via a Python-Flask web application. Results indicate the morning fare stabilizes at IDR 12,000 after a peak of IDR 14,500, while the noon fare remains constant at IDR 12,000. The evening period shows the highest volatility, peaking at IDR 14,342 (17:30 WIB, non-rainy) and IDR 21,250 (18:45 WIB, rainy). Accuracy evaluation across 21 paired data points from morning and evening sessions yielded MAE = IDR 1,047.62, MSE = 4,117,767.24, and RMSE = IDR 2,029.23, representing an 8.7% average error relative to the IDR 12,000 base fare. This margin confirms linear interpolation serves only as a rough baseline reference tool, not a reliable predictive model.